Nature of Communication Ineffectiveness Inherent in the Procurement Systems on Mass Housing Projects. (23rd November 2015) - Kwofie, Titus Ebenezer; Adinyira, Emmanuel; Fugar, Frank
Abstract : Mass housing projects (MHPs) are deemed to exhibit unique procurement systems which consequently induce communication ineffectiveness that continues to dominate the challenges among mass housing project teams. However, this acknowledged communication ineffectiveness inherent in the unique procurement system features of mass housing project among the project team remains to be empirically examined. This study seeks to investigate the influence of procurement system (PS) features of MHPs to communication ineffectiveness among the mass housing project team. By adopting a quantitative method design, a structured questionnaire survey on project team leaders managing MHPs in Ghana was used in collecting empirical data. Structural equation modeling (SEM) was used to explore the communication problems inherent in the PS features of mass housing projects. The results revealed moderate to high effects of communication ineffectiveness in information flow and information composition inherent in the unique PS features of MHPs. The results further revealed misunderstanding, inaccuracies, barriers, and information dissemination challenges as the major communication ineffectiveness induced by the PS features of MHPs. By gaining knowledge and understanding into the communication ineffectiveness associated with these features of MHPs, practitioners are well positioned to plan communication and management strategies to engender success in mass housing delivery.